Analysis and Mapping of Technical Competency Needs for TVET Teachers in the Era of Industry 4.0 - Widaningsih, Lilis; Rahayu, Sri; Dwiyanti, Vina; Widanengsih, Wiwi; Muktiarni (Journal of Technical Education and Training, 2025)
Vocational education in Indonesia still faces challenges, especially regarding limited teacher access to technical competency training due to industry needs. This study aims to map and analyze the access of Vocational High School (SMK) teachers to technical training in 10 areas of expertise in West Java. The method used is quantitative descriptive with a survey of 356 productive teachers from a population of 3,254. Measurement of technical competency refers to the Indonesian National Qualification Framework (KKNI) Level IV Certification Scheme. The study results show that teacher access to training is still low, with only 32.4% of 130 competency units accessed. Training organized by the government through the Center for the Development of Vocational Education Quality Assurance (BBPPMPV) has only been accessed by 19.4% of teachers, while 13% accessed training independently. Digital competency is the skill with the lowest achievement in all areas of expertise. This low access to training impacts the skills gap between teachers and industry needs, which has implications for the readiness of SMK graduates to face the world of work. These findings emphasize the need for an upskilling model based on industry needs involving government, industry, and training institutions. Increasing the frequency and quality of training can be done through industry-based schemes, digital platforms, and blended learning. In addition, strategic policies that ensure equal access to training for teachers in various regions are important to improve the quality of vocational education. This step is expected to improve the skills of productive vocational school teachers so that they are more relevant to technological developments and industry demands.